2021
DOI: 10.1097/won.0000000000000774
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Microbiological Outcomes Associated With Use of Platelet-Rich Plasma in Chronic Venous Leg Uclers

Abstract: PURPOSE:To evaluate the susceptibility profi les of Staphylococcus aureus and Pseudomonas aeruginosa strains identifi ed in chronic venous ulcers treated with platelet-rich plasma (PRP) and petrolatum gauze or petrolatum gauze alone and to quantitatively evaluate the bacterial load and biofi lm-forming capacities of the detected S. aureus and P. aeruginosa strains. DESIGN: Randomized controlled trial. SUBJECTS AND SETTING:The convenience sample included 36 participants; 18 were allocated to the PRP combined wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Pires, et al (2021) 13 At the conclusion of the 12-week treatment period, both the PRP (P = 0.0078) and control groups (P = 0.01) experienced a reduction in wound infections. The microorganisms were susceptible to the vast majority of antimicrobials tested.…”
Section: Resultsmentioning
confidence: 98%
“…Pires, et al (2021) 13 At the conclusion of the 12-week treatment period, both the PRP (P = 0.0078) and control groups (P = 0.01) experienced a reduction in wound infections. The microorganisms were susceptible to the vast majority of antimicrobials tested.…”
Section: Resultsmentioning
confidence: 98%
“…Seven studies assessed the rate of infection, 21,25,26,31,32,35 finding no significant difference between the two groups (OR = 0.89, 95% CI: 0.38–2.07, I 2 = 0%; Figure 8).…”
Section: Resultsmentioning
confidence: 99%
“…Ultimately, 16 RCTs were included in the meta-analysis (Figure 1). [18][19][20][21][25][26][27][28][29][30][31][32][33][34][35][36]…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, some researchers found that chronic wounds in the PRP group showed bright red granulation after 4 weeks of treatment, which was helpful to reduce inflammation exudation [ 61 ]. Pires et al [ 62 ] found that there was a similar amount of bacteriological growth in the excretion culturing of the PRP and normal saline dressing groups. These results confirmed the mechanisms of PRP, i.e., that growth factors from PRP could reduce local inflammation and promote angiogenesis and tissue regeneration around the wound.…”
Section: Discussionmentioning
confidence: 99%